Determinación de la calidad migratoria de rupela albinella, en época de secano, en la zona de Babahoyo - Vera Veas, Joffre Martín (2013)
The present investigation was carried out in the lands of the experimental farm San Pablo Agricultural Ability of Sciences of the Technical University of Babahoyo, located in the km 7 ½ via Babahoyo Montalvo with coordinated geographical of 79º34 south latitude, 01º49 latitude west, in a height of 8 m.s.n.m the area presents a climate of tropical type, with a half temperature to one of 25,6ºC, with a precipitation of 2.329m.m, with a relative humidity of 82% It was looked for to establish the migratory quality of Rupela albinella in the area of Babahoyo. To carry out this investigation you proceeded to count females of Rupela albinella a trap the same one that was located to 0.5 meter high this trap it was lit at 18H00 o'clock and out at 06H00 in the following day. It was made gatherings newspapers during 90 days (three months). after having captured the insects (female) they were taken to the laboratory in some recipients (it packs of glass).